Distributed manufacturing as an opportunity for service growth in logistics firms. Issue 3 (14th December 2020) - Purvis, Laura; Lahy, Andrew; Mason, Robert; Wilson, Mike
Abstract : Purpose: The aim of the paper is to explore the changing role of a logistics service providers (LSPs) to better support their supply chain (SC) partners on their journey of advancing their product-service systems through distributing manufacturing around the world. The purpose of this paper is to investigate a novel route towards service growth followed by the LSP by integrating upstream into the value chain and the resultant consequences in the configuration of the servitisation strategy, SC structure and allocation of roles. Design/methodology/approach: A longitudinal exploratory case study design is followed. The case company is one of the world's largest LSPs. Findings: The study highlights how companies can transition towards the development of service solutions when not following a uni-directional, downstream pattern of integration in the value chain. The findings challenge the established model of servitisation as a forward uni-directional process across the continuum from goods to a service-focussed logic. They illustrate how companies can also move in a reversed direction, move possible back-and-forth or extend and restrict their position along the servitisation continuum. Originality/value: The study reveals that service transition involves a deliberate developmental process to build capabilities as firms shift the focus of their product-service offering. It provides novel empirical evidence of how the service growth journey can manifest itself in practice. With insights into the benefits and challenges of distributed manufacturing, it also highlights some of the opportunities available to LSPs to expand their product-service offerings and some of the potential threats.